UTILIZING PROFESSIONAL TERMINOLOGY IN ENGLISH LESSONS - Azamat Bozorov Nazar ogli (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
The article presents a methodology for teaching English terminology in the direction of the masters of "Chemical Technology" and introduces the methods of teaching undergraduates of engineering universities using the Internet sites and materials.